Building a Strong Brand: Marketing Strategy to Increase Brand Awareness and Consumer Loyalty - Ian Zulfikar (International Publisher (YAPENBI), 2022)
Building a strong brand and increasing brand awareness and consumer loyalty is a key focus for business success. This study aims to describe effective marketing strategies to build strong brands and increase brand awareness and consumer loyalty. The research was conducted by conducting a literature review from various sources related to marketing strategy. The research findings show that some effective marketing strategies in building a strong brand are brand differentiation, use of social media, product and service development, and customer experience. By implementing these strategies in business practices, companies can strengthen brands and increase brand awareness and consumer loyalty.